The Economic Value Of Mangrove Forest Ecotourism In Apar Village, Pariaman City, West Sumatra: Nilai Ekonomi Ekowisata Hutan Mangrove Di Desa Apar Kota Pariaman Sumatera Barat - Gusna Merina (INOVASIA, 2023)
Before the mangrove forest in Apar Village was used as a tourist destination today, the community considered mangrove forests as wilderness plants that had no clear function and benefits that were never maintained. Many mangroves died due to drought and logger by the community for firewood to be far from sustainable. To manage and preserve the mangrove ecosystem, several efforts have been made, one of which is by quantifying the environmental services provided by the mangrove ecosystem. One of the environmental services of the mangrove forest ecosystem is the benefits of ecotourism. The results showed that the economic value of ecotourism in the mangrove forest covering an area of 10.62 hectares in Apar Village was Rp. 3,614,335.60 per year or Rp. 340,332.92 per Ha per year.